Light and Electron Microscopic Observations in the Rat Thyroid Following Experimental Hypothyroidism - Kükner, Aysel; Öner, Jale; Öner, Hakan; Çolakoğlu, Neriman; Özoğul, Candan; Ozan, Enver (Fırat University, 2001)
Mast cells have importance not only in their familiar role in acute allergic and parasitic diseases but also in chronic inflammatory, immunologic and fibrotic states. In addition they effective on thyroid gland function and the regulation of thyroid blood flow and capillary permeability. In this experimental study, hypothyroidism was induced by 10 mg/kg 6-n-propyl-2-thiouracil (Sigma), dissolved in 0.5 ml of 0.9 M saline, injected to 5-6 weeks old female rats intraperitoneally. Rats were sacrified after 15 days and thyroid glands were taken for light and electron microscopic studies. In the experimental groups, we observed changes in the follicular structure, along with decreased colloid , increased mitotic activity and intrathyroidal mast cells. At the ultrastructural level dilated GER was observed in the epithelial cell cytoplasm with on and increase in the intercellular spaces. Apoptotic cells were not observed in the follicular epithelial cells.

Mast hücreleri sadece akut allerjik ve parazitik hastalıklarda değil kronik enfeksiyonlarda, immünolojik ve fibrotik olaylarda da önemlidir. Ek olarak tiroid bezinin fonksiyonunda mast hücrelerinin rolü vardır. Tiroid mast hücreleri, TSH veya TRH nın salgılanmasında aktif rol oynamaktadır ve tiroid kan akımını ve kapiller geçirgenliğin düzenlenmesinde etkili olmaktadır. Bu deneysel çalışmada, 5-6 haftalık dişi sıçanlara intraperitoneal olarak 10mg/kg 6-n-propyl-2-thiouracil (Sigma), 0.9M serum fizyolojik içinde eritilmiş ilaçtan 0.5 ml verilerek hipotiroidizm oluşturuldu. 15 gün sonra sıçanlar sakrifiye edildi ve ışık ve elektron mikroskobik çalışmalar için tiroid bezi alındı. Deney grubunda, follikül yapılarının değiştiği, kolloid maddesinin azaldığı, mitotik aküvite artışı ve mast hücre artışı gözlendi. İnce yapı düzeyinde epitel hücrelerinin sitoplazmasında GER yapılarının çok fazla genişlediği, hücreler arası açılmaların arttığı gözlendi. Follikül epitel hücrelerinde apoptotik hücreler seçilemedi.
DENEYSEL HİPOTİROİDİ OLUŞTURULMUŞ SIÇAN TİROİD BEZİNDEKİ YAPISAL DEĞİŞİKLİKLERİN IŞIK VE ELEKTRON MİKROSKOBİK İNCELENMESİ